Введение в экспериментальную психологию: пер. с фр. - Бине А. Альфред; Анри В. Виктор; Филипп Ж. Жан; Куртье Ж. Жуль; Максимова А. И.; Введенский А. И. Александр Иванович (Санкт-Петербург, Типография П. П. Сойкина, 1895)
Дозволено цензурою. С.-Петербург, 13 ноября 1895 г.